Characterization of sandy soils in Campinaranas in the metropolitan region of Manaus, Amazonas - Sanches, Giulia Ketlen; Salviano, Olendina da Silva; Braga, Ítalo Gomes; Adjeran, Oloukemi Karmen Jocelyne [UNESP]; Tavares, Rafael Koide; Junior, Afrânio Ferreira Neves; Lima, Hedinaldo Narciso (Revista Brasileira de Geografia Fisica, 2024)
Sandy soils occurring near urban centers are impacted by mining activities. In Amazonas these areas are associated with the vegetation known as Campinaranas, which have an ecological importance, and makes it crucial to expand knowledge for development of restoration plans. This study aimed to characterize and classify sandy soils under Campinaranas in two cities in the metropolitan region of Manaus. Five areas of sandy soils were selected in Manaus and Presidente Figueiredo, where profiles were opened for morphological, chemical, physical, and mineralogical characterization. Profiles 01, 02, and 03 were classified as NEOSSOLO QUARTZARÊNICO Órtico típico, 04 as ESPODOSSOLO HUMILÚVICO Órtico dúrico, and 05 as NEOSSOLO QUARTZARÊNICO Órtico espodossólico. These soils had very friable consistency and a texture ranging from sandy loam to sand, with a predominance of fine sand. Clay content was low, resulting in low density and high porosity. The acidity ranged from strongly acidic to extremely acidic, with higher concentrations of H+Al and Al3+ in the surface horizons. Total organic carbon was more concentrated in the surface horizons and in the spodic horizon of P04. Effective and total cation exchange capacities (CEC) were also higher in the surface horizons and in the Bh (P04) and C4 (P05) horizons. Regarding mineralogy, higher proportions of crystalline forms of Al2O3 and Fe2O3 were found compared to amorphous forms, especially in the Bh (P04) horizon and in organic matter aggregates in P03, indicating the current process of podzolization and the influence of Al in the spodic formation in this soil.
Caracterização de solos arenosos em Campinaranas da região metropolitana de Manaus, Amazonas
Keywords: Arenosols; Ecological restoration; Podzols